Innovating and contextualising career counselling for young people during the Covid-19 pandemic. (June 2021) - Maree, Jacobus Gideon
This article reports on how the changing career counselling needs of young people during the Covid-19 pandemic can be met. It is argued that innovative and contextualised career counselling that is in line with the basic principles of 'best practice' and draws on a life design–based framework offers a viable conceptual framework for this kind of endeavour. Such counselling can promote young people's adaptability; enhance their employability; and bolster their narratability, narrativity and autobiographicity. A brief theoretical overview explains innovation and contextualisation in career counselling and clarifies key aspects of counselling for self- and career construction. The style of e-career counselling advocated here can help young people make meaning of their career-lives and (re-)kindle their sense of hope and purpose. Moreover, it can help them devise practicable strategies to actuate their sense of purpose and hope and also help them experience a sense of being part of something much bigger than themselves. In addition, it can promote young people's entrepreneurship and self-entrepreneurship and bolster their employability. Longitudinal research, including qualitative, quantitative and mixed-methods studies on the topic, is needed to examine the value of the e-career counselling approach. Such research could involve different assessment instruments and counselling strategies and include questionnaires to facilitate pre- and post-assessment of the effectiveness of the approach.